An Analysis of the Evolution, Power and Functions of the Native Authority System in Northern Nigeria - Zubairu, Umar; Barnabas, Douglas (Kashere Journal of Humanities, Management and Social Sciences, 2022)
A lot has been written on the history of Native Authority system and indirect rule in Northern Nigeria. In spite of the advances in the understanding of this colonial system of administration, there is still room for greater understanding of the trajectories of the Native Authority system in Northern Nigeria. This paper, therefore, focuses on the re-examination of the nature, character and operations of the Native Authority (NA) system. It clarifies the meaning, essence, evolution and development of the system as an administrative arm of the colonial state. It shows that for the workability of the NA system, there had to be an indigenous large central political system, which the British administrators converted to their advantage and use. In this regard, the Caliphate system in pre-colonial Sokoto was adapted and grafted into the NA System. The paper reveals that the system was not an independent administrative system, but part of the British colonial administrative machineries, which was externally determined and geared towards exploitation, oppression and domination of Nigeria. Thus, the functions of the Native Authority officials such as the Emirs and Chiefs, Judges (Alkali), Natives Police, Native Prisons and other NA staff were to maintain the British colonial laws and collect British taxes and implement colonial economic policies.